PENGARUH HARGA DAN KUALITAS PRODUK SMARTPHONE OPPO RENO TERHADAP KEPUASAN KONSUMEN DI ERAFONE MERUYA SELATAN JAKARTA BARAT - Agung Prasetia; Cornelia Dumarya Manik (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of price and product quality Oppo Reno on consumer satisfaction at Erafone Meruya Selatan, West Jakarta. This research method uses quantitative descriptive. The number of samples used was 105 respondents using the Simple Random Sampling Technique. Data collection techniques in this research used a questionnaire. The analysis in this research uses SPSS software version 27. The results of this research are Price (X1) on Consumer Satisfaction (Y), the regression obtained is Y = 2,119 + 0,927 X1. The tcount value is 13.527 > ttable 1.660, thus the results of the H1 hypothesis are accepted. In the variable Product Quality (X2) on Consumer Satisfaction (Y), the regression obtained Y = 1,450 + 0,955 X2 The value of tcount is 17.531 > ttable 1.660, thus the results of hypothesis H2 are accepted. Simultaneously with the variables Price (X1) and Product Quality (X2), the regression obtained Y = -1,793 + 0,330 X1 + 0,698 X2 . The Fcount value is 117.673 > Ftable 3.091, thus the results of the H3 hypothesis are accepted.